PEMBERDAYAAN UMKM SALE PISANG MELALUI PEMANFAATAN LIMBAH KULIT PISANG DI DESA PENGADANGAN, LOMBOK TIMUR - Guyup Mahardhian Dwi Putra; Gagassage Nanaluih De Side; Diah Ajeng Setiawati; Wiharyani Werdiningsih; Fakhrul Irfan Khalil; Wenny Amaliah (Jurnal AbdiMas Nusa Mandiri, 2026)
Pengadangan Village is one of the major banana-producing centers in East Lombok Regency, with a thriving banana processing industry led by the Bale Sentosa Banana Sales SME. This production activity generates organic waste in the form of banana peels and product byproducts that have not yet been fully utilized. This community service initiative aims to enhance the knowledge and skills of SME practitioners in managing banana peel waste into liquid organic fertilizer (POC) through the use of a simple composting device. The activity was carried out through the stages of preliminary survey, outreach, training, evaluation, and mentoring involving 20 members of the Bale Sentosa SME. Evaluation was conducted using pre-test and post-test methods to measure participants’ increased understanding. The results of the activity showed an increase in participants’ understanding from an average of 52% before training to 88% after training. A total of 15 kg of banana peel waste was successfully processed using a simple composter, yielding approximately 8 liters of liquid organic fertilizer during the fermentation process. Participants were also able to operate the composters independently and understood how to utilize banana peel waste as a valuable product. The application of this appropriate technology contributes to reducing organic waste and has the potential to provide economic added value for MSMEs. This activity supports the implementation of circular economy principles and sustainable waste management among Banana Sale MSMEs in Pengadangan Village.